IMPLEMENTASI KEBIJAKAN PEMBANGUNAN SISTEM PENGELOLAAN AIR LIMBAH DOMESTIK TERPUSAT DI KOTA PEKANBARU TAHUN 2019-2020 - Rezita Mulyani; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The construction of the Integrated Domestic Waste Treatment System (SPALD-T) is expected to be completed by December 2020, but the construction of the project is not in accordance with the stipulated timeframe. This study aims to determine the policy implementation of what factors caused the implementation of the policy for the development of a Centralized Domestic Wastewater Management System in Pekanbaru City in 2019-2020 not as planned. The method used in writing this research is a qualitative approach. Meanwhile, the key informants used were 6 people. The method of data collection is by using interviews, and documentation. Meanwhile, the data analysis technique uses (1) data reduction, (2) data presentation, and (3) conclusions. This research shows that: First: The implementation of the SPALD-T development has been quite implemented, this can be seen from several indicators, such as: 1) Ambiguity, the ambiguity problem occurs due to the length of time planning and implementation of the SPALD-T development, so that there have been many changes in the agency. Government, as well as environmental changes in each area that the pipeline network passes through. 2) Executors at the Frontline (implementing apparatus), the long time span between planning and implementation has also caused the implementers to have also undergone changes. 3) Funding and Resources. In addition, the funding and resources used are still not optimal, such as the human resources used are not much from the local area. Second: Obstacles in the implementation of the SPALD-T development are: Lack of socialization to the community, Planning for SPALD-T does not pay attention to the contours of the land that will be passed by the SPALD-T pipeline, In planning and timing of implementation also does not pay attention to weather conditions. Keywords:  Implementation, Centralized Domestic Wastewater Management System, Pekanbaru